PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT. SUMBER ALFARIA TRIJAYA TBK - Gea, Apolnius Gea; Mulyadi, Mulyadi (LPPM Swadaya Institute of Business and Communication, 2024)
This study aims to determine how much influence promotion and service quality have on purchasing decisions. The research method used in this study is a survey, with random sampling data collection techniques. Analysis using multiple linear regression with SPSS Version 24.00 program. The research variables are promotion and service quality as independent variables and purchasing decisions as the dependent variable. The results showed that the relationship between promotion variables and service quality had a major nfluence on purchasing decisions.